2018
DOI: 10.1097/01.aoa.0000542379.72599.86
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect of Ultrasound-guided Quadratus Lumborum Block After Cesarean Delivery: A Randomized Clinical Trial

Abstract: (Anesth Analg. 2018;126:559–565) Ultrasound (US)-guided transversus abdominis plane (TAP) blocks, although widely used for postoperative analgesia in inferior abdominal wall incision surgeries, are known to provide inferior analgesia when compared to neuraxial morphine and other multimodal regimens. A modified quadratus lumborum (QL) block technique, with injection at the posterior border of the QL muscle, may provide better and longer lasting analgesia compared with US-guided anterior TAP blocks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 15 publications
2
37
1
Order By: Relevance
“…To our knowledge, this is the first study that has compared the addition of quadratus lumborum block to a standard postoperative analgesic regimen that included intrathecal morphine. The benefits of quadratus lumborum block for pain relief after caesarean section in patients who have not received intrathecal morphine are notable . However, we did not find any additional analgesic benefit with quadratus lumborum block in the setting of intrathecal morphine administration.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…To our knowledge, this is the first study that has compared the addition of quadratus lumborum block to a standard postoperative analgesic regimen that included intrathecal morphine. The benefits of quadratus lumborum block for pain relief after caesarean section in patients who have not received intrathecal morphine are notable . However, we did not find any additional analgesic benefit with quadratus lumborum block in the setting of intrathecal morphine administration.…”
Section: Discussioncontrasting
confidence: 70%
“…There is potential to use a higher concentration such as levobupivacaine 0.375% with a volume increased to the maximum safe dose. The addition [11,12]. We are unsure of the true mechanism of action of the quadratus lumborum block and the postulation of local anaesthetic consistently tracking into the paravertebral space has been called into question [4,14,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of patients with opioid sparing effects in our study suggests that the analgesic effect of QLB can last 6 to 10 hours, but not 24 or 48 hours as previously reported. 20 This result is similar to the ndings of Mieszkowski MM, et al 21 , Krohg A, et al 22…”
Section: Discussionsupporting
confidence: 88%
“…21 A 2018 study by Krohg A, et al did not identify any clinically relevant opioid-sparing effect attributable to QLB during the 24 to 48-hour period. 22 Tamura T, et al reported the duration of the sensory loss in their study did not exceed eight hours after the posterior QLB, even at the anterior axillary line. 13,17 Different QLB approaches with respect to the ideal point of injection may result in unequal block effects.…”
Section: And Tamuramentioning
confidence: 73%